Red and blue nation? Volume 1 : characteristics and causes of America's polarized politics - Nivola, Pietro S.; Brady, David W. ([Stanford, Calif.] : Hoover Institution on War, Revolution, and Peace, Stanford University ; Washington, D.C. : Brookings Institution Press, 2006)
"Considers the extent to which polarized views among political leaders and activists are reflected in the population at large. Pays particular attention to factors such as the increased influence of religion and the changing nature of the media and offers thoughtful analyses of the underlying problems"--Provided by publisher
Characteristics and causes of America's polarized politics -- Delineating the problem / William A. Galston and Pietro S. Nivola -- Disconnected : the political class versus the people / Morris P. Fiorina and Matthew S. Levendusky -- Disconnected, or joined at the hip? / Alan I. Abramowitz, Gary C. Jacobson -- Rejoinder / Morris P. Fiorina and Matthew S. Levendusky -- Rejoinder / Alan I. Abramowitz -- Polarization then and now : a historical perspective / David W. Brady and Hahrie C. Han -- Polarization runs deep, even by yesterday's standards / James E. Campbell, Carl M. Cannon -- Polarized by God? : American politics and the religious divide / E.J. Dionne Jr. -- Myths and realities of religion in politics / Alan Wolfe, Andrew Kohut -- How the mass media divide us / Diana C. Mutz -- Two alternative perspectives / Thomas Rosentiel, Greg Easterbrook -- Polarizing the House of Representatives : how much does gerrymandering matter? / Thomas E. Mann -- Why other sources of polarization matter more / Gary C. Jacobson, Thomas B. Edsall.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Political parties -- United States; Party affiliation -- United States; Polarization (Social sciences); United States -- Politics and government; Partis politiques -- Adhésion -- États-Unis.; Polarisation collective; États-Unis -- Politique et gouvernement; POLITICAL SCIENCE -- Political Process -- Political Parties; POLITICAL SCIENCE -- Political Ideologies -- Conservatism & Liberalism; Party affiliation; Polarization (Social sciences); Political parties; Politics and government; United States